Salvage of Dental Implant Located in Mandibular Odontogenic Cyst. A Conservative Surgical Treatment Proposal - Antonio Troiano; Giorgio Lo Giudice; Roberto De Luca; Fabrizio Lo Giudice; Salvatore D'Amato; Gianpaolo Tartaro; Giuseppe Colella (MDPI AG, 2020)
The aim of this case report was to evaluate the use of Partsch I cystotomy in order to preserve a dental implant located in an odontogenic cyst extended from 3.2 to 4.4. A 50 year-old woman showed a circular, well-defined unilocular radiolucent area, Ø2.5 cm, in the right mandibular region with an oral implant intruding inside it. The overdenture in the mandibular right site showed no clinical mobility. The authors decided to perform a surgical treatment aimed to preserve the implant. The patient underwent Partsch I surgery followed by iodoform gauze insertion replaced weekly for one month, revision of the previous orthograde endodontic treatments, and an acrylic resin obturator prosthesis application for the following two months. The twelve month follow-up showed no clinical mobility of the right lateral mandibular implant prostheses. Radiographical analysis revealed cystic lesion healing and perimplant bone regeneration. This report highlights the opportunity to apply cystotomy when the cyst involves a dental implant and undermines its stability. This possibility is offered by the peculiar clinical scenario where the implant was stabilized by the presence of a previous prosthetic fixation. Our study led to the application of an operative protocol that allowed for the preservation of the implant.